EP.TH.625Consenting for a Bedside Procedure: A Prospective Observational Analysis of Consenting Practice in the Surgical Emergency Admissions Unit of a District General Hospital. (28th October 2021) - Mishra, Shashwat; Davis, Heather; Balakumar, Charannya; Shrestha, Ashish
Abstract: Aims: Consent is necessary to enable patient autonomy and essential to providing good clinical care. Recent case law has grown around consent and practice guidance has evolved. This was a prospective, observational study consisting of two cycles. It investigated the quality of consent for bedside incision and drainage (I&D) procedures performed in the surgical emergency admissions unit (SEAU) at a district general hospital compared with GMC guidance. Methods: A prospective analysis of consent documentation was performed from August to September 2020. Data was gathered for quality of consent including risk and benefit discussions, local anaesthetic used, operation note documentation and procedure discussion. We communicated these results at a departmental level, increased awareness of available consent forms and placed them in more accessible locations. Data to see the benefit of these interventions were gathered from November 2020 to January 2021. Results: In cycle one, of 20 cases (n = 20), 5.0% had written consent documentation, and 75.0% had verbal consent documentation. 20.0% of cases had no consent documented. Following interventions, of 14 cases (n = 14), 57.1% of cases had written consent documentation, and 7.14% had verbal consent documentation. 35.0% of cases had no consent documented. Conclusion: This study highlighted a deviation from GMC guidance. Interventions have shown to increase the proportion of cases with written consent. Overall cases with no written evidence of consent remain high and further work is required to increase compliance. We aim to refine the interventions we have implemented in order to promote the highest quality of consent documentation.